Comparison of immunomodulatory activities in mice and guinea pigs of a synthetic desmuramyl peptidolipid triglymyc. - Leclerc, C D (1984)
A nonpyrogenic desmuramyl peptidolipid, 1-O-(L-alanyl-D-isoglutaminyl-L-alanyl-glycerol-mycolate), had previously been shown to be inactive as adjuvant in guinea pigs, but to be very active in stimulating nonspecific resistance. We now show that 1-O-(L-alanyl-D-isoglutaminyl-L-alanyl-glycerol-mycolate) is capable of enhancing or suppressing the immune responses in mice when injected with or before an antigen. In vivo suppression of the immune response to sheep erythrocytes was also observed with high doses of murabutide, a nonpyrogenic adjuvant-active N-acetylmuramyl-L-alanyl-D-isoglutamine analog. Chemiluminescence measurements with mouse spleen cells show a very strong activity of 1-O-(L-alanyl-D-isoglutaminyl-L-alanyl-glycerol-mycolate) by far superior to the effect obtained with the corresponding muramyl peptide, N-acetylmuramyl-L-alanyl-D-isoglutaminyl-L-alanyl-glycerol-myco late.